Propuesta de un plan de marketing estratégico dirigido al mercado de la ciudad de Loja, para la empresa Y&J soluciones médicas - Girón Soto, Ivony Gardenia (2024)
The present research work aims to elaborate a proposal for a strategic marketing plan to the market of Loja city directed to the company Y&J Medical Solutions, in order to be able to identify objectives and strategies to increase sales, improve positioning and propose a strategic plan for it; Therefore, it is based on a theoretical and conceptual framework. Regarding the research methodology, the method used was: descriptive, inductive, deductive, based on the use of the interview and surveys, and information was collected and evaluated through different matrices of external factors MEFE, matrix of internal factors MEFI, matrix of MPC competitive positioning. The findings evidenced in these data reflect a decrease in interest rates, state-of-the-art technology in technological advances in medicines and medical supplies; among the main threats it was found an increase in monthly inflation and a decrease in purchasing power, and a high level of rivalry between competitors. The internal analysis made possible to identify strengths such as service quality, products and prices. Weaknesses such as lack of market research, lack of advertising and low market share were also identified. Once all the analyzes were completed, the SWOT matrix was made, which allowed the design of strategies; the proposal of the strategic plan was made where it is located, the business philosophy, structural organization chart, strategic and operational objectives of the plan and budget. This proposal will serve as a guide for the management of the company, in decision- making, currently being the best positioned company "Dicimed S.A.S" which turns into direct competition; Therefore, the company hopes to attract a greater number of clients through the implementation of the plan based on strategies that allow the company to selectively develop and improve.